2015
DOI: 10.2131/jts.40.727
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent acceleration in the delayed effects of neonatal oral exposure to low-dose 17α-ethynylestradiol on reproductive functions in female Sprague-Dawley rats

Abstract: -Xenoestrogen exposure during the critical period of sexual differentiation of the brain causes delayed effects on female reproduction. We investigated the internal dose of orally administered ethynylestradiol (EE) during the critical period and its delayed effects by administering 0 (vehicle control), 0.4, or 2 μg/kg EE to female Sprague-Dawley rats for 5 days from postnatal day (PND) 1. Determination of serum EE level 24 hr after the initial dosing and 6 and 24 hr after the final dosing of 2 μg/kg indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Previously, we demonstrated that neonatal exposure to diethylstilbestrol (DES) accelerated onset of abnormal estrous cycles in female Sprague-Dawley (SD) rats (Ohta et al, 2012a) and female C57BL/6J mice (Ohta et al, 2014) as they aged, suggesting the importance of observing estrous cycles over a long period in research on endocrine disrupting chemicals (EDCs). Similarly, other investigators suggested that neonatal exposure to DES in Donryu rats (Yoshida et al, 2011) and to 17alpha-ethynylestradiol in SD rats (Shirota et al, 2012;Shirota et al, 2015) or Wistar Hannover rats (Takahashi et al, 2013) induced delayed effects on their estrous cycles. It was proposed that abnormal development of kisspeptin neurons plays a key role in early onset of abnormal estrous cycles in rats (Ichimura et al, 2015;Takahashi et al, 2016).…”
Section: Introductionmentioning
confidence: 82%
“…Previously, we demonstrated that neonatal exposure to diethylstilbestrol (DES) accelerated onset of abnormal estrous cycles in female Sprague-Dawley (SD) rats (Ohta et al, 2012a) and female C57BL/6J mice (Ohta et al, 2014) as they aged, suggesting the importance of observing estrous cycles over a long period in research on endocrine disrupting chemicals (EDCs). Similarly, other investigators suggested that neonatal exposure to DES in Donryu rats (Yoshida et al, 2011) and to 17alpha-ethynylestradiol in SD rats (Shirota et al, 2012;Shirota et al, 2015) or Wistar Hannover rats (Takahashi et al, 2013) induced delayed effects on their estrous cycles. It was proposed that abnormal development of kisspeptin neurons plays a key role in early onset of abnormal estrous cycles in rats (Ichimura et al, 2015;Takahashi et al, 2016).…”
Section: Introductionmentioning
confidence: 82%
“…Previous studies have already demonstrated the influence of ethinylestradiol on the stages of estrous cycle of female rodents, with delay or late onset being observed in females exposed to certain concentrations of exogenous estradiol analogs. 55 Among the endocrine mechanisms involved in the development and maintenance of the corpus luteum, the elevated plasma estrogen concentration from the preovulatory follicle stands out as a preponderant factor, as it determines a preovulatory peak of LH and, consequently, ovulation and luteinization. Likewise, estradiol is also related to the degeneration of the structure of the corpus luteum, since they are related to the secretion of PGF2-a, a substance responsible for, among other effects, decreasing blood flow to the corpus luteum and degeneration of its capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, estradiol is also related to the degeneration of the structure of the corpus luteum, since they are related to the secretion of PGF2-a, a substance responsible for, among other effects, decreasing blood flow to the corpus luteum and degeneration of its capillaries. 13,55,56 In gerbils, females that have not copulated present a rapid involution of the corpus luteum within 3 to 6 days after their formation. However, remaining luteal cells may be present for longer periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in fishes, EE 2 is concentrated multiple times (480-720) relative to water [35]. Studies on terrestrial mammals at concentrations similar to the contraceptive dose of 400-800 ng/kg/day or lower are relatively scarce: administration of EE 2 during development can affect a variety of reproductive anatomical and physiological endpoints in mice and rats [20,[36][37][38][39][40][41][42][43][44][45][46] but see a lack of effects with 500 ng/kg/day in Mandrup et al [34].…”
Section: Introductionmentioning
confidence: 99%